Hydrodynamic and hydrochemical levels of groundwater in perennial crops of the Vinces canton, Los Ríos, Ecuador - Veliz, Freddy; Calle , Kleber; Maruri , Diego; Navarro , Ivan; Rodríguez, Fanny; Veliz , Maritza (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
The static and dynamic levels, as well as the quality of groundwater sources used for agricultural production, represent an important factor in understanding the characteristics of the use of wells for this activity and the influence on the decline in static levels during the dry season. The objective of this research was to determine the behavior of the hydrodynamic and hydrochemical levels of groundwater used in plantain, banana, and cocoa production to improve water resource utilization in the Clariza parish of the Vinces canton, Ecuador. Data were collected from 10 production units in the area. For the dynamic levels, a constant-rate pumping test was performed. For water quality characteristics, in-situ tests for pH, electrical conductivity (EC), and total dissolved solids (TDS) were performed, and no values ​​were recorded that would restrict their use for agricultural activities. The declines in dynamic levels were constant and progressive during the dry season due to the irrational use of water through pumping systems. Dynamic levels measured using the pumping test determined maximum drawdowns between 6 and 8 m in depth; however, well recovery showed constant rising levels, indicating aquifer recharge.